The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1113/jp272036
|View full text |Cite
|
Sign up to set email alerts
|

Divergent in vivo activity of non‐serotonergic and serotonergic VGluT3–neurones in the median raphe region

Abstract: Key points The median raphe is a key subcortical modulatory centre involved in several brain functions, such as regulation of the sleep–wake cycle, emotions and memory storage.A large proportion of median raphe neurones are glutamatergic and implement a radically different mode of communication compared to serotonergic cells, although their in vivo activity is unknown.We provide the first description of the in vivo, brain state‐dependent firing properties of median raphe glutamatergic neurones identified by im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 61 publications
2
22
0
Order By: Relevance
“…The molecular features of specific serotonin cell types suggest their functional properties. For example, several studies have reported that subgroups of serotonin neurons in the MR and DR express Vglut3 and indeed, subsequent slice recording confirmed that serotonin terminals can co-release glutamate and serotonin (Domonkos et al, 2016; Liu et al, 2014; Ren et al, 2018; Sengupta et al, 2017; Varga et al, 2009; Wang et al, 2019). In addition to neurochemical properties, each serotonin neuron population expresses a specific combination of distinct genes responsible for electrophysiological (ion channels), connectivity (wiring molecules), and functional (neurotransmitter/peptide receptors) properties (Figure 4; Figure 4—figure supplement 1A).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The molecular features of specific serotonin cell types suggest their functional properties. For example, several studies have reported that subgroups of serotonin neurons in the MR and DR express Vglut3 and indeed, subsequent slice recording confirmed that serotonin terminals can co-release glutamate and serotonin (Domonkos et al, 2016; Liu et al, 2014; Ren et al, 2018; Sengupta et al, 2017; Varga et al, 2009; Wang et al, 2019). In addition to neurochemical properties, each serotonin neuron population expresses a specific combination of distinct genes responsible for electrophysiological (ion channels), connectivity (wiring molecules), and functional (neurotransmitter/peptide receptors) properties (Figure 4; Figure 4—figure supplement 1A).…”
Section: Discussionmentioning
confidence: 93%
“…The majority of the clusters express Slc17a8 , which encodes vesicular glutamate transporter-3 (Vglut3). These include almost all serotonin neurons from the cDR, the majority from MR clusters (Domonkos et al, 2016), and DR-3–6 clusters (Figure 1D). These observations suggest that glutamate is the most prevalent co-transmitter for serotonin neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Our results demonstrate that LH GABA neurons directly inhibit DR GABA neurons and this probably results in a disinhibition of various DR neurons. Revealing the exact targets of this disinhibition awaits further investigation and are hard to predict given the extreme neurochemical and physiological diversity of the raphe nuclei (Domonkos et al, 2016; Szonyi et al, 2016; Sos et al, 2017). A phasic increase in 5-HT neuron activity can rapidly and prominently affect cortical activity (Lottem et al, 2016) and thus may lead to brain state changes.…”
Section: Discussionmentioning
confidence: 99%
“…VGLUT3 + /5-HT + neurons may be a specialized 5-HT subtype as these cells were found to have specific electrophysiological signatures in patch clamp analyses, with lower activation thresholds, suggesting that they may be recruited only by strong stimuli to boost serotonergic/glutamatergic signals (59). Further, in vivo recordings indicated that VGLUT3 + /5-HT − , VGLUT3 − /5-HT + , and VGLUT3 + /5-HT + neurons in the MRN possess significantly different firing rates, responses to sensory stimulation, and phase coupling to forebrain oscillations (82).…”
Section: -Ht Neuron Molecular Identitymentioning
confidence: 99%